HUBUNGAN PENGETAHUAN IMUNISASI MR DAN SOSIAL BUDAYA TERHADAP MOTIVASI IBU DALAM KEIKUTSERTAAN IMUNISASI MR - Mauludiyah, Zaida; Yulita, Hendra; Yanti, Lilis Candra; Noorma, Nilam; Yuliawati, Dwi (Ensiklopedia of Journal, 2024)
The incidence of measles and rubella in Indonesia has increased every year. In 2015, there were 6,209 cases, in 2016 there were 7,204 cases and in 2017 there were 11,389 cases. Rubella cases in 2015 were 1,379 cases, in 2016 were 1,170 cases and in 2017 were 4,349 cases. Surveillance data for the last 5 years shows 70% of Rubella cases occur in the age group <15 years To realize the highest degree of public health, efforts are needed to prevent the occurrence of a disease through immunization. The purpose of this study was to determine the relationship of MR immunization knowledge and socio-culture to maternal motivation in MR immunization participation. This type of research is quantitative, using analytic corellational design with Cross Sectional approach. Statistical analysis shows there is a relationship between knowledge and maternal motivation in MR immunization participation (P-value 0.001), there is a significant relationship between social culture and maternal motivation in MR immunization participation (P-value 0.002). From the results of the research that has been carried out, it can be concluded that there is a significant relationship between knowledge of MR immunization and socio-culture on maternal motivation to participate in MR immunization in the working area of Puskesmas Tambang.Keywords: MR immunization, Motivation, Knowledge, Socio-culture